2022
DOI: 10.3390/su141912303
|View full text |Cite
|
Sign up to set email alerts
|

Renovating Building Groups in the Mediterranean Climate: Cost-Effectiveness of Renewable-Based Heating Alternatives in the Italian Context

Abstract: District level approaches for the renovation of the building stock boost the implementation of energy efficiency measures (EEMs), taking advantage of the economies of scale. International Energy Agency Annex 75 aims to assess the cost-effectiveness of renovation strategies at the district level, combining EEMs and renewable energy sources. For this goal, a building energy model is simulated with the Energy Plus dynamic calculation engine for assessing the generic district of the Italian case study, representin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…The energy balance simulation results demonstrated that replacing the existing windows yielded the highest final energy savings. This corroborates the findings of [14,17,22], who analyzed implementations of EEMs in multi-apartment buildings located in similar climate conditions as the studied building. This indicates the vital role of windows as the largest contributor to heat losses in buildings in winter and the potential for a broader implementation of this EEMs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The energy balance simulation results demonstrated that replacing the existing windows yielded the highest final energy savings. This corroborates the findings of [14,17,22], who analyzed implementations of EEMs in multi-apartment buildings located in similar climate conditions as the studied building. This indicates the vital role of windows as the largest contributor to heat losses in buildings in winter and the potential for a broader implementation of this EEMs.…”
Section: Discussionsupporting
confidence: 90%
“…A major challenge in energy renovation projects is to achieve energy efficiency requirements cost effectively [12,13]. Different studies [14][15][16][17][18][19][20][21][22][23][24] have investigated the economic benefits of EEMs for existing buildings. Dodoo et al [17] found that adding insulation to the basement walls is the most cost-effective EEM for a multi-apartment building located in southern Sweden.…”
Section: State Of the Artmentioning
confidence: 99%
“…It is important to highlight that, for this case study, neither the order of results nor the magnitude of global costs and primary energy consumption changed for the two simulated climates. However, it is noteworthy that P01 (passive-only solutions) was not cost-effective for I1V2 (Lisbon) but approached the cost-effectiveness threshold for I2V1 (Porto), characterised by colder winters, where insulation is more critical to reduce thermal losses [42,43].…”
Section: Resultsmentioning
confidence: 99%